Enhancing the effectiveness of data management to improve data quality for evidence-based decision-making : a case study of Pelonomi Tertiary Hospital - Malahleha, Mafumane Alice (Stellenbosch : Stellenbosch University, 2024)
Thesis (MPA)--Stellenbosch University, 2024.